2011
DOI: 10.1007/s10327-011-0340-z
|View full text |Cite
|
Sign up to set email alerts
|

Talaromyces wortmannii FS2 emits β-caryphyllene, which promotes plant growth and induces resistance

Abstract: A plant-growth-promoting fungus (PGPF), Talaromyces sp. was isolated from an agricultural field in southwestern Japan. We found that this fungus emitted several terpenoid-like volatiles including b-caryophyllene. Then we investigated the effect of b-caryophyllene on promoting the growth and inducing resistance of Brassica campestris L. var. perviridis. The compound significantly enhanced the growth of seedlings and their resistance to Colletotrichum higginsianum. On the basis of these results, we discuss the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
60
2
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 106 publications
(63 citation statements)
references
References 32 publications
0
60
2
1
Order By: Relevance
“…Ryu et al [10] first reported that the microbial VOCs 2,3-butanediol and acetoin promoted the growth of Arabidopsis thaliana. PGPF-derived VOC mediated growth promotion in plants was first reported by Yamagiwa et al [11]. VOCs of certain PGPFs including the biocontrol fungus Trichoderma have been shown to enhance plant growth [7,11].…”
Section: Introductionmentioning
confidence: 99%
“…Ryu et al [10] first reported that the microbial VOCs 2,3-butanediol and acetoin promoted the growth of Arabidopsis thaliana. PGPF-derived VOC mediated growth promotion in plants was first reported by Yamagiwa et al [11]. VOCs of certain PGPFs including the biocontrol fungus Trichoderma have been shown to enhance plant growth [7,11].…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, Yam‐agiwa et al. also demonstrated an increased growth of Brassica campestres seeds in the presence of Colletotrichum higginsianum . The same authors also reported an increase in B. campestres resistance using the same pathogen.…”
Section: Resultsmentioning
confidence: 81%
“…Furthermore, a fuel potential has been ascribed to this compound [20]. In addition, β-cariophyllene is produced by F. oxysporum MSA 35 [42] and Talaromyces wortmannii [3,46]. This sesquiterpene could enhance plant growth and induce tolerance or resistance to the fungal pathogens Colletotrichum higginsianum and Botrytis cinerea.…”
Section: Ecological Function and Biological Activity Of Identified Vocsmentioning
confidence: 97%